Acceptability of a Professional School of Accountancy. - Kublin, Milton (The Accounting Review, 1965)
In the opinions of the groups surveyed, there was no general agreement as to the acceptability of or the current need for professional schools of Accountancy similar to schools of Medicine or Law. There was, however, good support for such a school among Certified Public Accountants, accounting teachers, and business executives. Most certified public accountants believed that professional schools of accountancy would make a contribution to both the public and private field of accountancy. Deans believed clearly that present schools of business are adequate for the formal education of professional accountants and that there is no need for separate schools of accountancy. Corporate executives appeared to favor separate schools of accountancy. However, the majority of opinions of the executives indicated no current need for a separate school of accountancy. University and college presidents favored the present schools of business and indicated that accreditation of the department of accountancy within a school of business would be acceptable. A majority of accounting professors believed that in most areas of the organizational structure for the formal education of professional accountants a professional school of accountancy might be the most effective means. All groups favored an extension of the current four-year program for the formal education of professional accountants.